Inculcating Digital Contents, Technological Tools: Agents for Enhancing Business Education Curriculum for Skill Acquisition in Nigerian Universities - C. C., Ufondu; V. C. , Udeh; C. M., Amobi (Online Journal for TVET Practitioners, 2023)
This study was on inculcating digital contents, technological tools as agents for enhancing business education curriculum for Skill Acquisition in Universities in Anambra State. Two research questions and null hypotheses were tested at a 0.05 level of significance. The study adopted a descriptive survey research design. A population of 34 business educators in Universities in Anambra state were used for the study. No sample was drawn for the study since the size of the population is manageable. The instrument used to collect data for the study was a structured questionnaire with two parts; part A contained items on the demography of respondents and part B contained items on the two research questions under the study. The questions were structured on a 5 point rating scale of Strongly Agree (SA); Agree (A), Moderately Agree (MA), Disagree (D) and Strongly Disagree. The instrument was validated b three experts, two from the Department of Business Education and one from Measurement and Evaluation. Cronbach Alpha reliability coefficient was used to test consistency of the instrument and a general coefficient of 0.81. Data collected was analyzed using arithmetic mean and standard deviation while t- test was used to test the hypotheses at 0.05 level of significance. When the p value was found to be equal or less than 0.05 alpha levels, the noted difference was said to be significant, therefore, the null hypothesis was be rejected. However, a p value found to be greater than 0.05, the noted difference was insignificant, therefore, the null hypothesis will be accepted. The findings of the study revealed that business education lecturers in universities in Anambra state agree that provision of instructional technology, inculcating digital contents can enhance business education curriculum for skill acquisition. These findings were discussed and conclusion was drawn. Relevant recommendations were made based on the findings of the study part of which included that Management of business education programme should incorporate digital tools and platforms that are relevant to various business disciplines, such as data analytics software, marketing automation platforms, project management tools, or simulation software. Provide hands-on training and practical exercises using these tools to develop students’ proficiency in digital technologies applicable to the business context